BiF3 octahedrons: A potential natural solar light active photocatalyst for the degradation of Rhodamine B dye in aqueous phase. (April 2019) - Ritika,; Kaur, Manjot; Umar, Ahmad; Mehta, Surinder Kumar; Kansal, Sushil Kumar
Graphical abstract: Highlights: Facile synthesis and detailed characterizations of BiF3 octahedrons. BiF3 octahedrons used for the photocatalytic degradation of Rhodamine B dye under natural solar light irradiation. BiF3 octahedrons exhibited ˜95.7% degradation of RhB in aqueous phase in 50 min under natural solar light irradiation. Abstract: Herein, we report the successful synthesis of BiF3 octahedrons via facile hydrothermal process as potential solar light active catalyst for the photocatalytic degradation of Rhodamine B (RhB) dye in aqueous phase. The synthesized BiF3 octahedrons were characterized by several techniques such as X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), transmission electron microscope (TEM), Fourier transform infrared (FT-IR) spectroscopy, UV-diffuse reflectance spectroscopy (UV-DRS), photoluminescence (PL) spectroscopy, thermogravimetric analysis (TGA) and Brunauer-Emmett-Teller (BET) techniques in order to observe the structural, morphological, optical and luminescence properties. The synthesized octahedrons possess the high density growth, pure and well-crystalline with cubic phase structure and band gap of 3.98 eV. As a potential solar light active photocatalyst, the synthesized BiF3 octahedrons exhibited ˜95.7% degradation of RhB in 50 min. The effect of different process parameters such as pH and catalyst dose on the degradation of RhB was also explored. Interestingly, the synthesized BiF3 octahedrons demonstrated better photocatalytic performance compared to several commercially available photocatalysts such as TiO2 (PC-500), SnO2 and ZnS. Further, it was observed that the degradation of RhB over the prepared BiF3 octahedrons obeyed the pseudo first-order reaction kinetics with rate constant of 0.06393 min −1 . The scavenger experiments verified the role of h +, e, O2, OH and OHs in the photocatalytic degradation process and a plausible photocatalytic mechanism has also been proposed.